Effect of ECAP numbers on microstructure and properties of titanium matrix composite. (15th June 2015) - Han, Yuanfei; Li, Jiuxiao; Huang, Guangfa; Lv, Yuting; Shao, Xi; Lu, Weijie; Zhang, Di
Graphical abstract: Highlights: (TiC + TiB)/Ti composite was successfully obtained by up to four passes of Equal Channel Angular Pressing (ECAP). Homogeneous distribution of refined TiB + TiC reinforcement particles was achieved. Maximum tensile strength was obtained after 4 ECAP passes. The microhardness was found to increase with the number of ECAP extrusion passes. Abstract: In this study, equal channel angular pressing (ECAP) of (TiB + TiC)/Ti6Al4V titanium matrix composite was successfully carried out at 800 °C, the effect of pass number on the microstructure and mechanical properties was investigated. After each pass of ECAP, the evolution of the microstructure and mechanical properties of (TiB + TiC)/Ti6Al4V composite during thermal-mechanical processing was studied, the Vickers micro-hardness measurements and tensile testing were performed at room temperature. The results showed that the size of the reinforcements and grains were both fully refined to a smaller scale, a number of more homogeneous TiB short fibers and TiC particles have been attained after four ECAP passes. The tensile strength increased with increasing ECAP numbers and saturated after four ECAP passes to a yield strength of 1200 MPa, and microhardness was also significantly improved by means of this processing technology, the ductility of titanium matrix composite after the four ECAP passes was slightly greater than the first ECAP pass.